Snakes : the evolution of mystery in nature - Greene, Harry W., 1945- (University of California Press, 1997)
"This is a book about some of nature's most alluring and forbidding creatures, written by a man with an abiding passion for snakes, as well as for science, conservation, and the beauty and complexity of nature. Snakes inhabit all major ecosystems outside of the polar regions and are among the most common predators on other vertebrates. More than 2,700 species of snakes are currently recognized, place in about 420 genera and 18 families ..."